Sulfonyl covalent organic framework material, preparation method thereof and humidity sensor
The sulfonic acid-based covalent organic frame material was prepared through interface polymerization and combined with quartz crystal microbalances, which solved the problem of insufficient stability and water retention of existing humidity sensors, and achieved a humidity sensor with high sensitivity and good sensing performance.
Patent Information
- Application Number
- CN202510272440.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-10
AI Technical Summary
The existing humidity sensors have poor stability in high-demand scenarios, and the metal organic frame materials are not stable enough under water-containing conditions, which affects the detection accuracy.
Interface polymerization is used to prepare sulfonic acid-based covalent organic frame material and combine it with quartz crystal microbalance to form a humidity sensor. The material has good water retention and controllable preparation conditions.
It has achieved a humidity sensor with good stability, high sensitivity and good sensing performance, and has good response and recovery capabilities in the humidity range of 11%~97%.
Smart Images

Figure CN119775517A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of gas humidity sensing, and in particular to a sulfonic acid covalent organic framework material, a preparation method thereof and a humidity sensor. Background Art
[0002] Covalent organic framework materials (COF) are a type of crystalline porous polymer material composed of organic molecules connected by covalent bonds. COFs have the characteristics of low density, high specific surface area, and are easy to modify and functionalize. Therefore, they are widely used in gas storage and separation, heterogeneous catalysis, photoelectric transmission, drug delivery and sensing. In the field of humidity sensing, humidity sensing is currently mainly based on the change of color and impedance of COFs at different humidity levels. For example, Pal et al. synthesized COF-TXDBA through Schiff base reaction, which can detect environmental humidity through changes in COFs impedance, but this humidity detection method is relatively cumbersome.
[0003] The humidity sensor consists of three parts: a humidity sensing device, a conversion device and a measurement circuit. Its working principle is mainly to use the conversion element to convert the measured humidity into a physical quantity that is easy to analyze, and then measure it by the instrument. At present, the commonly used humidity sensors are mainly electrical humidity sensors, optical humidity sensors and mass humidity sensors. The sensing of electrical humidity sensors depends on the change of electrical signals. Although it has the advantages of simple structure and low cost, its stability is poor and it cannot be used in high-demand scenarios; optical humidity sensors have the advantages of fast response speed and high sensitivity, but due to principle limitations, optical humidity sensors have poor anti-interference ability.
[0004] Mass humidity sensors are based on the mass effect of sensitive elements and are made by utilizing the relationship between the oscillator parameters (frequency, amplitude, wave velocity, etc.) of a specific piezoelectric crystal and the changes in its surface mass. They have the advantages of strong anti-interference ability and a wide range of applications.
[0005] The Chinese invention patent with publication number CN109883877A discloses a quartz crystal microbalance and humidity sensor based on metal organic framework materials (MOF). The humidity sensor uses MOF materials as humidity sensitive materials and combines them with quartz crystal microbalance to make humidity sensors. The humidity sensor can detect humidity in the ppm range. However, metal organic framework materials are porous materials based on metal-organic coordination bonds, and the strength of chemical bonds is limited, resulting in a stability bottleneck in the application of MOF materials. Especially under water-containing conditions, metal ions are prone to hydration reactions with water molecules, which in turn affects the pore structure of MOF and may significantly reduce the detection accuracy of humidity sensors.
[0006] In addition, there is currently no precedent for applying COFs materials to mass-type humidity sensors. Summary of the invention
[0007] The object of the present invention is to provide a humidity sensor with good stability and high sensitivity based on a covalent organic framework material.
[0008] To achieve the above object, the first aspect of the present invention provides a method for preparing a sulfonic acid covalent organic framework material, which specifically comprises the following steps: S1: dissolving 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde in octanoic acid to prepare solution A; S2: dissolving 2,5-diaminobenzenesulfonic acid in water to prepare solution B; S3: Add solution B dropwise onto the upper layer of solution A and allow to react; S4: After the reaction is completed, the upper clear liquid is removed, and the lower red aqueous solution is dialyzed to obtain a sulfonic acid covalent organic framework material.
[0009] At present, the preparation methods of COFs include mechanical grinding, microwave synthesis and solvent thermal method, among which mechanical grinding and microwave synthesis can only be processed by direct tableting to form solid powder materials, and the COFs powder samples prepared by tableting have poor solubility, low conduction efficiency, and cannot be connected to the device. The solvent thermal method has high reaction temperature, long time and consumes a large amount of solvent, and has the defects of high energy consumption and high production cost. The present invention adopts interfacial polymerization to prepare sulfonic acid covalent organic framework materials, and the reaction conditions of the preparation method are mild. At the same time, the whole process conditions of synthesizing sulfonic acid covalent organic framework materials using this method are controllable.
[0010] Preferably, the molar ratio of the 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde to 2,5-diaminobenzenesulfonic acid is 1:(1-2).
[0011] The second aspect of the present invention provides a sulfonic acid covalent organic framework material prepared by the preparation method of the first aspect.
[0012] The sulfonate loading amount of the sulfonic acid covalent organic framework material provided by the present invention reaches more than 3.2 mmol / g, which makes the sulfonic acid covalent organic framework material provided by the present invention have good water retention.
[0013] The third aspect of the present invention provides a humidity sensor, which includes a quartz crystal microbalance and the sulfonic acid covalent organic framework material described in the second aspect, the quartz crystal microbalance includes an electrode, and the sulfonic acid covalent organic framework material is coated on part or all of the surface of the electrode of the quartz crystal microbalance.
[0014] The humidity sensor provided by the present invention combines the sulfonic acid covalent organic framework material of the second aspect with a quartz crystal microbalance for the first time, and the prepared humidity sensor has the advantages of high sensitivity and high precision of the quartz crystal microbalance sensor and good water retention of the sulfonic acid covalent organic framework material.
[0015] Preferably, the resonant frequency of the humidity sensor is 19-21 MHz.
[0016] Preferably, the coating amount of the sulfonic acid covalent organic framework material is at least 170 ng.
[0017] Preferably, the humidity sensor further comprises an oscillation circuit for collecting sensing data and a computer for processing the sensing data.
[0018] A fourth aspect of the present invention provides a method for preparing a humidity sensor, comprising the following steps: SA: Preparation of sulfonic acid covalent organic framework materials; SB: Preparation of aqueous solution of sulfonic acid covalent organic framework material; SC: The aqueous solution of sulfonic acid covalent organic framework material is dropped onto the electrode surface of the quartz crystal microbalance and a humidity sensor is obtained after drying.
[0019] Preferably, in step SB, the concentration of the aqueous solution of the sulfonic acid covalent organic framework material is 0.1-0.5 mg / mL.
[0020] In the preparation method of the humidity sensor, the sulfonic acid covalent organic framework material is directly coated on the surface of the quartz crystal microbalance. The preparation method has the advantage of simple operation.
[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a sulfonic acid covalent organic framework material, which has excellent water retention performance, so that the sulfonic acid covalent organic framework material has the potential to become a humidity sensitive material; 2. The preparation method of the sulfonic acid covalent organic framework material provided by the present invention has controllable parameters and mild reaction conditions, and has broad application prospects; 3. This invention combines sulfonic acid covalent organic framework materials with quartz crystal microbalance for the first time to produce a humidity sensor. The humidity sensor exhibits good sensing performance in the humidity range of 11% to 97%, providing new research ideas for the subsequent development of humidity sensors. 4. The preparation method of the humidity sensor provided by the present invention is simple to operate and has the potential for large-scale production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1The experimental results of the contact angle analysis in Example 3; Figure 2 The measurement result of the frequency response of the humidity sensor in Example 4; Figure 3 The response and recovery curves of the QCM-1 measured continuously in the lowest (11% RH) and highest (97% RH) humidity environments in Example 6; Figure 4 The response and recovery curves of the QCM-2 measured continuously in the lowest (11% RH) and highest (97% RH) humidity environments in Example 6; Figure 5 The response and recovery curves of the QCM-3 measured continuously in the lowest (11% RH) and highest (97% RH) humidity environments in Example 6; Figure 6 The response and recovery curves of the QCM-4 in Example 6 measured continuously under the lowest (11% RH) and highest (97% RH) humidity environments; Figure 7 The response and recovery curves of the QCM-5 measured continuously in the lowest (11% RH) and highest (97% RH) humidity environments in Example 6 are shown in FIG. Figure 8 : is the dynamic response characteristic curve of each humidity sensor in Example 7. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0024] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0025] Although it has been proven that porous materials such as MOFs combined with quartz crystal microbalance (QCM) have the potential to become humidity sensors, there are still no reports on humidity sensors based on covalent organic framework materials and QCM. Based on this, a specific embodiment of the present invention provides a method for preparing a sulfonic acid covalent organic framework material, which specifically includes the following steps: S1: dissolving 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde in octanoic acid to prepare solution A; S2: dissolving 2,5-diaminobenzenesulfonic acid in water to prepare solution B; S3: Add solution B dropwise onto the upper layer of solution A and allow to react; S4: After the reaction is completed, the upper clear liquid is removed, and the lower red aqueous solution is dialyzed to obtain a sulfonic acid covalent organic framework material.
[0026] In some specific embodiments, the molar ratio of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde to 2,5-diaminobenzenesulfonic acid is 1:(1-2).
[0027] The sulfonic acid covalent organic framework material prepared according to the above method has a sulfonate loading of more than 3.2 mmol / g, which makes the sulfonic acid covalent organic framework material have good water retention performance.
[0028] A specific embodiment of the present invention also provides a humidity sensor, which includes a quartz crystal microbalance and the aforementioned sulfonic acid covalent organic framework material, wherein the quartz crystal microbalance includes an electrode, and the sulfonic acid covalent organic framework material is coated on part or all of the surface of the electrode of the quartz crystal microbalance.
[0029] The humidity sensor of the above embodiment is manufactured by the following steps: SA: Preparation of sulfonic acid covalent organic framework materials; SB: prepare an aqueous solution of a sulfonic acid covalent organic framework material, wherein the concentration of the aqueous solution of the sulfonic acid covalent organic framework material is 0.1-0.5 mg / mL; SC: The aqueous solution of sulfonic acid covalent organic framework material is dropped onto the electrode surface of the quartz crystal microbalance and a humidity sensor is obtained after drying.
[0030] In the above embodiment, a sulfonic acid covalent organic framework material thin film can be formed on the surface of the quartz crystal microbalance electrode by dropping a sulfonic acid covalent organic framework material aqueous solution on the surface of the quartz crystal microbalance electrode and drying.
[0031] The working principle of the humidity sensor provided in the above embodiment is as follows: when the humidity sensor is in a humidity environment of 11% to 97% and the ambient humidity rises, the sulfonic acid covalent organic framework material film, which is a humidity-sensitive material, will absorb water and change its own mass due to the change in ambient humidity. The changed mass can be reflected according to the oscillation frequency of the quartz crystal microbalance. Therefore, the ambient humidity data can be obtained by reverse deduction only by collecting and measuring the change in the oscillation frequency of the quartz crystal microbalance through an oscillation circuit.
[0032] The technical scheme of the present invention is further described below by specific examples. Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, the terms with conventional understanding meanings are defined herein for the purpose of illustrating or facilitating quoting, and such definitions herein should not be construed as indicating that there are significant differences with conventional understandings in the art. The technical methods described herein or cited are generally fully understood by those skilled in the art and adopted by conventional methods. Unless otherwise stated, the use of commercially available reagents and instruments is carried out according to the schemes and parameters given by the manufacturer.
[0033] In a specific embodiment of the present invention, the saturated salt solution shown in Table 1 is used to provide the corresponding relative humidity.
[0034] Table 1
[0035] Example 1 Preparation of sulfonic acid-based covalent organic framework materials.
[0036] S1: 0.1 mM 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde was ultrasonically treated for 30 min and then dissolved in 20 mL of octanoic acid to prepare solution A; S2: 0.1 mM 2,5-diaminobenzenesulfonic acid was ultrasonically treated for 30 min and then dissolved in 30 mL of water to prepare solution B; S3: Add solution B dropwise onto the upper layer of solution A and allow to react at 20°C for 3 days; S4: After the reaction is completed, the upper clear liquid is removed and the lower red aqueous solution is dialyzed for 2 days to obtain a sulfonic acid covalent organic framework material dispersion. The concentration of the sulfonic acid covalent organic framework material is calibrated to 1 mg / mL by dry weighing method.
[0037] Example 2 Humidity sensor assembly.
[0038] The five quartz crystal microbalance (QCM) elements used in this embodiment are from Yangxing Technology, with a base frequency of 20MHz and a silver electrode diameter of 4mm. After the silver electrode is exposed, ethanol and water are used to clean the silver electrode to ensure that there is no dirt on the surface of the silver electrode. The frequency of the cleaned and dried QCM element is measured, and the relevant data is recorded.
[0039] The sulfonic acid covalent organic framework material dispersion prepared in Example 1 was diluted with ddH2O, and the concentrations of the diluted sulfonic acid covalent organic framework material solutions were 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, and 0.5 mg / mL, respectively.
[0040] The above five concentrations of sulfonic acid covalent organic framework material solutions were respectively added dropwise onto the surfaces of five quartz crystal microbalance silver electrodes. After drying in a vacuum oven at 85°C, humidity sensors were obtained. The five humidity sensors were labeled as QCM-1 (0.1 mg / mL), QCM-2 (0.2 mg / mL), QCM-3 (0.3 mg / mL), QCM-4 (0.4 mg / mL), and QCM-5 (0.5 mg / mL). The frequencies of the five humidity sensors were measured and recorded.
[0041] The above five humidity sensors were connected to the oscillation circuit board, and all components were stored in a dry container.
[0042] Example 3 Contact angle analysis.
[0043] The sulfonic acid covalent organic framework material solutions of five concentrations prepared in Example 2 were dripped onto a smooth quartz glass and dried to form a COF film. The contact angle of the corresponding COF film was measured using a contact angle meter. The relevant results are shown in Table 2 and Figure 1 shown.
[0044] Table 2
[0045] From Table 2 and Figure 1 It can be seen that as the mass of the sulfonic acid covalent organic framework material film increases, the water contact angle gradually decreases, which means that the hydrophilicity of the material gradually increases, which means that the covalent organic framework material provided by the present invention has good hydrophilicity.
[0046] Example 4 Frequency response.
[0047] Using the five humidity sensors prepared in Example 2, the change value of the sensor frequency was measured in a humidity environment of 11% to 97% and a linear fit was performed. The relevant experimental results are shown in Table 3 and Figure 2 As shown, Figure 2 A in is the frequency response curve of the corresponding humidity sensor under different humidity conditions. Figure 2 B in FIG. 1 is the frequency logarithmic fitting curve of the corresponding humidity sensor under different humidity conditions.
[0048] Table 3
[0049] From Table 3 and Figure 2It can be seen that under the ambient humidity of 11%~97%, the frequency shift of the five humidity sensors shows an upward trend with the increase of humidity, indicating that they have strong humidity sensing characteristics, and the frequency change values increase with the increase of the concentration of sulfonic acid covalent organic framework materials. The logarithm of the frequency change has a good linear fitting effect with the relative humidity, and the five humidity sensors have a good linear correlation coefficient.
[0050] Example 5 Sensitivity test.
[0051] The frequency values of five quartz crystal microbalances before and after coating the sulfonic acid covalent organic framework material film were measured using a frequency meter. Based on the simplified Sauerbrey equation (1), the film mass can be obtained. The relevant results are shown in Table 4.
[0052] It can be seen from the table that as the mass of the sulfonic acid covalent organic framework material film increases, the sensitivity of the humidity sensor tends to increase. Among them, the sensitivity is defined as the slope of the QCM frequency change and relative humidity fitting curve, which indicates the speed of the frequency output when the humidity changes. The calculation formula is shown in formula (1).
[0053] (1) In the formula, is the frequency change value, is the QCM fundamental frequency, 20 MHz, is the membrane mass, and A is the area of the QCM silver electrode.
[0054] Table 4
[0055] Example 6 Response-Recovery Time Determination.
[0056] The response-recovery time refers to the time required for the sensor frequency shift to reach 90% of the total frequency shift change during the process of moisture absorption and dehumidification. Figure 3 The response and recovery curves of the QCM-1 measured continuously in the lowest (11% RH) and highest (97% RH) humidity environments are shown; Figure 4 The response and recovery curves of the QCM-2 under continuous measurements in the lowest (11% RH) and highest (97% RH) humidity environments are shown; Figure 5 The response and recovery curves of the QCM-3 under continuous measurements in the lowest (11% RH) and highest (97% RH) humidity environments are shown; Figure 6 The response and recovery curves of the QCM-4 under continuous measurement in the lowest (11% RH) and highest (97% RH) humidity environments are shown; Figure 7The response and recovery curves of QCM-5 measured continuously in the lowest (11% RH) and highest (97% RH) humidity environments are shown. The response and recovery times of QCM-1, QCM-2, QCM-3, QCM-4, and QCM-5 are shown in Table 5. QCM-2 has excellent response / recovery performance (15s and 1s).
[0057] Table 5
[0058] Example 7 Determination of dynamic response characteristics.
[0059] Five humidity sensors were placed in the humidity generating device in sequence, and the humidity increased from the minimum humidity value of 11% RH to the maximum humidity value of 97% RH, and then decreased from the maximum humidity value of 97% RH to the minimum humidity value of 11% RH. The response time of each device was 10 minutes, and the dynamic response characteristic curve was as follows: Figure 4 As shown in Table 6, the reaction is basically stable after 10 minutes, and the result is more accurate. The humidity hysteresis measurement results of the humidity sensor in the range of 11% RH-97% RH are shown in Table 6. In the range of 11% RH-97% RH, the maximum humidity hysteresis is 15.40%.
[0060] Table 6
[0061] It can be seen from Table 6 that the humidity hysteresis of the humidity sensor provided by the present invention is better. The reason for the humidity hysteresis is that during the humidity increase process, due to the adsorption of water molecules in the salt solution, as the humidity increases, the adsorption amount of water molecules increases, the film thickness increases, and the output frequency of the sensor decreases. Conversely, during the decrease process, the adsorption amount of water molecules decreases, the film thickness decreases, and the vibration frequency of the sensor decreases. However, since the sulfonic acid covalent organic framework material film has adsorbed a certain amount of water molecules to form a surface state, the water molecules cannot be completely desorbed, and residues are formed on the surface of the sulfonic acid covalent organic framework material film, resulting in a low output frequency and hysteresis.
[0062] It can be seen from Examples 1 to 7 that the humidity sensor provided by the present invention has the advantages of good hydrophilicity, high sensitivity, fast response-recovery, and good dynamic response, and has broad application prospects.
[0063] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a sulfonic acid covalent organic framework material, characterized in that: The following steps are involved: S1: dissolving 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde in octanoic acid to prepare solution A; S2: dissolving 2,5-diaminobenzenesulfonic acid in water to prepare solution B; S3: Add solution B dropwise onto the upper layer of solution A and allow to react; S4: After the reaction is completed, the upper clear liquid is removed, and the lower red aqueous solution is dialyzed to obtain a sulfonic acid covalent organic framework material.
2. The preparation method according to claim 1, characterized in that The molar ratio of the 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde to 2,5-diaminobenzenesulfonic acid is 1:(1-2).
3. A sulfonic acid covalent organic framework material, characterized in that: The moisture-sensitive material is prepared by the preparation method described in claim 1 or 2.
4. A humidity sensor, characterized in that: The humidity sensor comprises a quartz crystal microbalance and the sulfonic acid covalent organic framework material according to claim 3, wherein the quartz crystal microbalance comprises an electrode, and the sulfonic acid covalent organic framework material is coated on a part or all of the surface of the electrode of the quartz crystal microbalance.
5. The humidity sensor according to claim 4, characterized in that The resonant frequency of the humidity sensor is 19-21 MHz.
6. The humidity sensor according to claim 4, characterized in that: The coating amount of the sulfonic acid covalent organic framework material is at least 170 ng.
7. The humidity sensor according to claim 4, characterized in that: The humidity sensor also includes an oscillating circuit for collecting sensing data and a computer for processing the sensing data.
8. A method for preparing the humidity sensor according to any one of claims 4 to 7, characterized in that: The following steps are involved: SA: Preparation of sulfonic acid covalent organic framework materials; SB: Preparation of aqueous solution of sulfonic acid covalent organic framework material; SC: The aqueous solution of sulfonic acid covalent organic framework material is dropped onto the electrode surface of the quartz crystal microbalance and a humidity sensor is obtained after drying.
9. The preparation method according to claim 8, characterized in that: In the step SB, the concentration of the sulfonic acid covalent organic framework material aqueous solution is 0.1-0.5 mg / mL.
Citation Information
Patent Citations
Metal organic framework material-based quartz crystal microbalance and humidity sensor
CN109883877A
Modified humidity-sensitive material, preparation method and application thereof, and humidity sensor
CN114644888A
Sulfonic acid functionalized covalent organic framework / Nafion proton exchange material as well as preparation method and application thereof
CN115084609A
Sensitive material based on covalent organic framework film, humidity sensor and preparation method thereof
CN115304808A
Method for preparing flame-retardant chinlon 6 fabric through in-situ deposition
CN118461317A